Emerging Roles of Strigolactones in Plant Responses to Stress and Development - Pandey, Amita; Sharma, Manisha; Pandey, Girdhar K. (Frontiers in Plant Science, 2016)
Our environment constantly undergoes changes either natural or manmade affecting growth and development of all the organisms including plants. Plants are sessile in nature and therefore to counter environmental changes such as light, temperature, nutrient and water availability, pathogen, and many others; plants have evolved intricate signaling mechanisms, composed of multiple components including several plant hormones. Research conducted in the last decade has placed Strigolactones (SLs) in the growing list of plant hormones involved in coping with environmental changes. SLs are carotenoid derivatives functioning as both endogenous and exogenous signaling molecules in response to various environmental cues. Initially, SLs were discovered as compounds that are harmful to plants due to their role as stimulants in seed germination of parasitic plants, a more beneficial role in plant growth and development was uncovered much later. SLs are required for maintaining plant architecture by regulating shoot and root growth in response to various external stimuli including arbuscular mycorrizal fungi, light, nutrients, and temperature. Moreover, a role for SLs has also been recognized during various abiotic and biotic stress conditions making them suitable target for generating genetically engineered crop plants with improved yield. This review discusses the biosynthesis of SLs and their regulatory and physiological roles in various stress conditions. Understanding of detailed signaling mechanisms of SLs will be an important factor for designing genetically modified crops for overcoming the problem of crop loss under stressful conditions.